# What is 6/7 - 2/6? getcalc.com's two fractions subtraction calculator is an online basic math function tool to find what's the equivalent fraction for difference between two fractional numbers with different, unequal or unlike denominators 6/7 and 2/6.

6/7 - 2/6 = 22/42 as simplified as 11/21 in fraction form

6/7 - 2/6 = 0.5238 in decimal form
This calculator, formula, step by step calculation and associated information to find the difference between 6/7 and 2/6 may help students, teachers, parents or professionals to learn, teach, practice or verify such two fractions subtraction calculations efficiently.

## How to Find Equivalent Fraction for 6/7-2/6?

The below workout with step by step calculation shows how to find what is the difference between two fractions by subtracting a fraction 2/6 from 6/7. For different, unequal or unlike denominators, use any one of the following methods to find the equivalent fraction for 6/7 minus 2/6.
1. LCM method
2. Cross multiplication method.

Problem and Workout - LCM Method
What is 6/7 minus 2/6 as a fraction by subtraction using LCM method?

step 1 Address formula, input parameters and values.
Input parameters and values:
6/7 & 2/6
6/7-2/6 = ?

step 2 For unequal denominators, find the LCM (least common multiple) for both denominators
The LCM for 7 and 6 is 42.

step 3 To have the common denominator, multiply the LCM with both numerator and denominator
=(6 x 42)/(7 x 42)-(2 x 42)/(6 x 42)
=36/42-14/42
=(36 - 14)/42

step 4 Find difference between numerators and rewrite it in a single form.
= 22/42
=11/21
6/7-2/6=11/21

By using LCM method, 11/21 is the equivalent fraction by subtracting 2/6 from 6/7.

Problem and Workout - Cross Multiplication Method
step 1 Address formula and input values.
Input values:
6/7 & 2/6
6/7 - 2/6 = ?

step 2 Cross multiply both numerator and denominator, multiply both denominators and rewrite as below
= (6 x 6) - (2 x 7)/(7 x 6)

step 3 Simplify and rewrite the fraction
= (36 - 14)/42
= 22/42
= 11/21
6/7-2/6 = 11/21
By using cross multiplication method, 11/21 is the difference between two fractions 6/7 and 2/6. 